2019
DOI: 10.22317/jcms.v5i6.681
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the link between pelvimetry based on computed tomography and predicting status’ delivery

Abstract: Objectives: The aim of this study is an anthropometric study in non-pregnant reproductive-aged women to predicting kind of delivery. Methods: This study was based on the archived information of Hazrat-e Rasool university hospital on 157 generative age women from 16 to 60 years old. who underwent CT between March of 2015 until March of 2018. Results: The obtained results showed that the three conjugates on sagittal plane, transverse diameter, anteroposterior sagittal diameter, interspinous diameter and intertub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Our study showed the prevalence of gynaecoid pelvis (46.66%) slightly lower than this study. 14 Differences in pelvic dimensions may occur due to an individual's locomotor activities and postural changes. Our study had a prevalence of gynaecoid pelvis lower than the study conducted on Sudanese women with 50.6%.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed the prevalence of gynaecoid pelvis (46.66%) slightly lower than this study. 14 Differences in pelvic dimensions may occur due to an individual's locomotor activities and postural changes. Our study had a prevalence of gynaecoid pelvis lower than the study conducted on Sudanese women with 50.6%.…”
Section: Discussionmentioning
confidence: 99%